Catastrophe preparation and prevention for fire service professionals - Baldwin, Craig (McGraw-Hill Higher Education, 2008)
Catastrophe Preparation and Prevention for Fire Service Professionals is a multi-media product for Homeland Security designed for fire service personnel. It features a full color, 160 page, spiral-bound worktext that contains a link to an online simulation game called “San Luis Rey” and a CD-ROM containing selected government documents and excerpts from McGraw-Hill texts. Instructors can use the wealth of material in the CD-ROM to adjust the length of the course. It can be taught in a single day or two-day course or expanded into a full semester. The worktext guides the student through the material and links the learning experience from the different formats.